Design and manufacture of a reinforced fuselage structure through automatic laying-up and in-situ consolidation with co-consolidation of skin and stringers using thermoplastic composite materials. Issue 1 (January 2023) - Martín, I.; Fernández, K.; Cuenca, J.; Sánchez, C.; Anaya, S.; Élices, R.
Abstract: Thermoplastic composites can be used to construct safer and more efficient aircraft fuselage structures. They provide significant weight reduction compared to conventional metallic materials, reducing the fuel consumption of the aircraft and increasing its performance and profitability. In this study, we designed and manufactured a level 2* flat fuselage specimen. The specimen comprises 2 Ω-shaped stringers and one Z-shaped frame that were manufactured using a carbon fibre-reinforced thermoplastic material. The skin was laminated on top of the stiffeners and co-consolidated to them, eliminating the need for rivets or adhesives. The manufacturing processes of the stiffeners (press-forming) and skin (in-situ consolidation) are described herein. The quality of the manufactured specimens was evaluated through non-destructive and physical–chemical testing. The test results will serve as a reference for designing and manufacturing a level 3* curved fuselage in a future study. *Level 2: "Element tests according to the Building Block approach (MIL-HDBK-17, 2002) [18]"; Level 3: "Detail tests according to the Building Block approach (MIL-HDBK-17, 2002) [18]".